Digital vascular lesions detected by transillumination - Pyeritz, Reed E. (American journal of medical genetics. Part A, 2022)
Abnormalities of the capillaries of the digits in hereditary hemorrhagic telangiectasia can be detected by shining through a narrow beam of light through the dorsal side and visualizing the vasculature on the palmar side, a procedure termed transillumination. This study was performed to determine if this method can detect digital vascular abnormalities in aortopathies and arteriopathies. Transillumination was performed in patients with Marfan syndrome (MFS), thoracic aortic aneurysm and dissection (TAAD), vascular Ehlers–Danlos syndrome (vEDS), bicuspid aortic valve with aortopathy, and arteriopathies without aortopathy. Subjects with no known vascular disorders were controls. Digital vascular abnormalities were present in some patients with all of the disorders and were especially frequent in MFS, TAAD, and vEDS. All patients had significantly more digital vascular abnormalities than control subjects. Transillumination can detect vascular abnormalities in digits of patients with a variety of conditions with aortopathy or arteriopathy.